Search for extraplanar radio emission in a sample of edge-on starburst galaxies - Galante, Camila Ailen (2024)
The intense star formation in starburst galaxies results in the formation of intense winds that sweep matter up to several kpc out of the galactic plane. These winds can be detected in many bands of the electromagnetic spectrum. In this opportunity, we present our project to study three edge-on galaxies, candidates to show extraplanar emission at radio wavelengths. We will describe the criteria followed in selecting the sample and the software developed to detect the presence of the wind. Besides, we will discuss the next steps of this project.